The Allure of Consensus and the Perseverance of Minority: Aspects of Democracy in the Hellenistic World - Buraselis, Kostas (Classica et Mediaevalia, 2026)
If majority may count as the moving force, minority (and its distinct existence) is the distinctive quality of democracy. They are both precious components of a Herakleitian ‘balanced harmony’ (παλίντροπος ἁρμονίη), which one should always consider and respect in democratic practice. This maxim is studied on the basis of various testimonies from the Hellenistic period of ancient Greek history, when democracy underwent various limitations.